2020
DOI: 10.1111/pde.14446
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric drug reaction with eosinophilia and systemic symptoms: A systematic review of the literature, with a focus on relapsing cases

Abstract: Background: Drug reaction with eosinophilia and systemic symptoms (DRESS) is a severe cutaneous adverse drug reaction with systemic symptoms. This study aims to investigate clinical features, causative drugs, and available treatments for pediatric DRESS, particularly for relapsing cases. Methods: A systematic search of the English and French literature on pediatric DRESS was conducted using the Medline, Embase, and Cochrane collaboration databases. Confirmed cases of pediatric DRESS fulfilling the RegiSCAR dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
12
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 22 publications
5
12
1
2
Order By: Relevance
“…In our case, piperacillin-tazobactam and amikacin were the potential inciting drugs for DRESS syndrome. Moris et al reported piperacillin-tazobactam in only two of the 103 cases of DRESS syndrome (2%) but was rarely reported by others [ 1 , 5 , 11 ]. To the best of our knowledge, amikacin has not been reported as a triggering drug for DRESS syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our case, piperacillin-tazobactam and amikacin were the potential inciting drugs for DRESS syndrome. Moris et al reported piperacillin-tazobactam in only two of the 103 cases of DRESS syndrome (2%) but was rarely reported by others [ 1 , 5 , 11 ]. To the best of our knowledge, amikacin has not been reported as a triggering drug for DRESS syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…In mild disease (no organ involvement or only mild liver involvement), treatment is symptomatic. Systemic corticosteroids, immunosuppressive medications, and intravenous immunoglobulins are reserved for severe cases with significant visceral organ injury, particularly renal and/or pulmonary involvement [ 1 , 11 ]. In our patient, progressive resolution of clinical features and laboratory abnormalities (inflammatory markers, eosinophils, and decrease in hepatic enzymes) was observed within two days of ceasing piperacillin-tazobactam and amikacin treatment, highlighting the importance of early recognition and prompt removal of inciting drugs to avoid harmful outcomes associated with DRESS syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…DRESS is a complex disorder characterized by the onset of severe dermatological lesions along with hypersensitivity features, and the involvement of an internal organ, frequently the liver [65]. In a recent systematic review including 144 case reports and case series with 354 reported paediatric DRESS cases, nearly 60% of children were treated with systemic corticosteroids, while 13% received intravenous immunoglobulins (IVIg) [66]. In addition, in a case series of 49 well defined DRESS cases (84% with liver injury), corticosteroids (topical for mild cases, and systemic for more severe cases) were the main therapeutic option, whereas IVIg and cyclosporin were used only in a limited number of cases [67].…”
Section: Discussionmentioning
confidence: 99%
“…En nuestro caso, la piperacilina-tazobactam y la amikacina fueron los posibles fármacos desencadenantes del síndrome DRESS. Moris et al señalaron la presencia de piperacilina-tazobactam en sólo dos de los 103 casos de síndrome DRESS (2%), pero otros autores lo reportaron en raras ocasiones [1, 5, 11]. Hasta donde sabemos, no se ha reportado que la amikacina sea un fármaco desencadenante del síndrome DRESS.…”
Section: Discusión Y Conclusionesunclassified
“…En los casos leves (sin afectación orgánica o con afectación hepática leve), el tratamiento es sintomático. Los corticosteroides sistémicos, los medicamentos inmunosupresores y la administración intravenosa de inmunoglobulinas se reservan para los casos graves, con lesión significativa de órganos viscerales, especialmente compromiso renal y/o pulmonar [1, 11]. En nuestro paciente se observó una resolución progresiva de las características clínicas y las anomalías de laboratorio (marcadores inflamatorios, eosinófilos y disminución de las enzimas hepáticas) a los dos días de suspender el tratamiento con piperacilina-tazobactam y amikacina, lo que pone de relieve la importancia de un reconocimiento temprano y un rápido cese de los fármacos desencadenantes.…”
Section: Discusión Y Conclusionesunclassified